Pengaruh Latihan Shooting Sasaran Tetap dan Sasaran Berubah Dengan Media Latihan Ban Bekas Terhadap Ketepatan Shooting (Studi Kasus : Siswa SSB Putra Podorejo U-12 2022) - Muhamad Arifudin; Mohamad Annas; Ranu Baskora Aji Putra; Dwi Gansar Santi Wijayanti (Indonesian Journal for Physical Education and Sport, 2024)
Shooting is one of the basic techniques for creating goals if done accurately. Target practice is one thing to train the shooting accuration. This research aims to determine the effect of shooting practice at fixed targets and changing targets using used tires on shooting accuracy. The metode that used is experiment quantitative metode. The sample of this research is 24 students of Putra Podorejo Football-School U-12 which is divided to experiment class and control class using A-B-B-A pattern. Based on the research results obtained average pre-test for the experiment class 9,16 post-test 15,91 the mean differences is 6,75 from tcount = 6,787 ≥ ttabel = 1,812. The average of the control class is 9,08 post test is 13,75 the different mean is 4,67 for tcount = 4,304 ≥ ttabel = 1,812 with level α= 0,05 Ho rejected and Ha accepted. Post test average difference test for experimet class and control class is 15,91-13,75 = 2,16 with tcount 2,095. The conclusion of this research is there is a significant effect of shooting practice at fixed targets and changing targets using used tires on shooting accuracy